Next‐Generation Immunosequencing Reveals Pathological T‐Cell Architecture in Autoimmune Hepatitis. Issue 4 (8th February 2021) - Schultheiß, Christoph; Simnica, Donjete; Willscher, Edith; Oberle, Anna; Fanchi, Lorenzo; Bonzanni, Nicola; Wildner, Nils H.; Schulze Zur Wiesch, Julian; Weiler‐Normann, Christina; Lohse, Ansgar W.; Binder, Mascha
Abstract : Background and Aims: Autoimmune hepatitis (AIH) is a chronic liver disease that regularly relapses when immunosuppression is tapered. It is thought to be driven by T‐cells, whereas the etiologic impact of an apparently deregulated B lineage system, as evidenced by hypergammaglobulinemia and autoantibodies, remains elusive. We set out to investigate T and B cell repertoires supporting chronic inflammation in AIH. Approach and Results: T and B cell receptor (TCR/BCR) and human leukocyte antigen (HLA) next‐generation immunosequencing were used to record immune signatures from a cohort of 60 patients with AIH and disease controls. Blood and liver B lineage immune metrics were not indicative of a dominant directional antigen selection apart from a slight skewing of IGHV ‐J genes. More importantly, we found strong AIH‐specific TRBV‐J skewing not attributable to the HLA‐DRB1 specificities of the cohort. This TCR repertoire bias was generated as a result of peripheral T cell (de)selection and persisted in disease remission. Using a clustering algorithm according to antigenic specificity, we identified liver TCR clusters that were shared between patients with AIH but were absent or deselected in patients with other liver pathologies. Conclusions: Patients with AIH show profound and persisting T‐cell architectural changes that may explain high relapse rates after tapering immunosuppression. Liver T‐cell clusters shared between patients may mediate liver damage and warrant further study.